Evolução das internações hospitalares, decorrentes do uso abusivo de álcool e outras drogas, no período de 2008 a 2015 - Silva, Francisco Carlos Lins da (2016)
Among all the causes of hospital admissions due to mental and behavioral disorders, abusive use of alcohol and other drugs represents one of the main reasons for hospitalizations. The growing number of users, and especially of drug dependents, makes abusive use of alcohol and other drugs a global public health problem. Thus, the present study had as objective to analyze the evolution of hospital admissions, due to abusive use of alcohol and other drugs, carried out in the State of Alagoas, from 2008 to 2015. An analytical, observational study of the ecological type was carried out, based on the information found in the national databases Of the Hospitalization System of the Unified Health System (SIH / SUS). Averages, proportions and gross rates were calculated. Among the first ten causes of hospitalizations due to mental disorders, the use of some type of drug is the second largest responsible (15.10%), second only to hospitalizations by Schizophrenia (57.25%). When specifically observed hospitalizations due to the use of drugs, it is verified that the disorders generated by the abuse of alcohol and multiple drugs concentrate 99,17% of hospitalizations. There was a strong trend of growth in these hospitalizations (R² = 0.8419), an increase of 90.56% when compared to the extremes of the evaluated period, regardless of the sex considered. In population terms, when the population is considered as a reference, in relation to the number of hospitalizations, there is no shocking increase related to these causes. However, in comparison to the other causes of mental disorders, an important increase in the accomplishment of such hospitalizations has been observed. Comparatively, men are the majority among hospitalizations for alcohol abuse (p = 0.0000), while women are more susceptible to the use of hypnotic sedatives (p = 0.0000), cocaine (p = 0.0000), volatile solvents (p = 0.0000), stimulants (p = 0.0000) and the use of multiple drugs (p = 0.0000). No difference was observed regarding the use of cannabinoids (p = 0.6283) and opiates (p = 0.0080). The volume of hospitalizations for alcohol and other drugs abuse is increasing, and it is necessary to elaborate and implement multisectoral preventive strategies, since this situation is directly related to the Social Determinants of Health.